Electropalatographic specification of Croatian fricatives /s/ and /z - Liker, Marko (Array, 2012)
Electropalatographic specification of alveolar fricatives in Croatian is aimed at providing speech therapists with normative data about the range of acceptable productions of /s/ and /z/ in adult speakers of Croatian. Four variables were analysed: place of articulation, total contact, groove width and hold phase duration. Intraspeaker and interspeaker variability for each variable were analysed. Lingual palatal cues for voicing difference were also quantified and discussed. Results show that Croatian /s/ and /z/ are alveolar and not dental as previously reported. The comparison between the voiced and the voiceless fricative shows that durational measures provide the best differentiation. The voiceless counterpart is significantly longer. The difference between voiced and voiceless is also found in the total contact, with /z/ having more contact in the anterior four rows of electrodes, while /s/ has more contact in the posterior four rows of electrodes. This difference is also reflected in the anterior and the posterior groove width. Possibilities of using these results as normative data for the diagnosis and treatment of atypical articulation of /s/ and /z/ are discussed.